Eficacia del ozono en la cicatrización de heridas postquirúrgicas no contaminadas en perros y gatos de dos clínicas veterinarias “Biomedicina Veterinaria las Lomas” y “Perla del pacífico” de la ciudad de Guayaquil. - Olivo Macías, Yuly Melissa (2019)
The healing of post surgical wounds, represent a problem in the daily clinic, due to its recovery and the time to heal, which may affect the quality of life of the patient and its owner, therefore the present work is carried out with the purpose to promote the use of ozone therapy in the veterinary clinic, having as objective to determine the healing effect of ozone in post-surgical non-contaminated wounds in dogs and cats comparing two methods. To achieve the proposed objectives, the study subjects were divided into two groups, the first group was worked in the veterinary clinic "Las lomas", for which the topical method was used and in the clinic "Perla del Pacífico" the subdermal method was used. , with a total of 71 animals, the following were evaluated: border variables, vascularity, erythema and exudate on days 3 and 5 post surgery, for its analysis the percentage method and statistical tests were used (T student and T paired), having a level of significance of 0.05, revealing as a result that there are significant differences between the subdermal and topical treatments, the subdermal treatment being the one that presented the best response to its use, as well as the healing and bactericidal properties of ozone.